2015
DOI: 10.1038/onc.2015.338
|View full text |Cite
|
Sign up to set email alerts
|

RUNX3 is a novel negative regulator of oncogenic TEAD–YAP complex in gastric cancer

Abstract: Runt-related transcription factor 3 (RUNX3) is a well-documented tumour suppressor that is frequently inactivated in gastric cancer. Here, we define a novel mechanism by which RUNX3 exerts its tumour suppressor activity involving the TEAD-YAP complex, a potent positive regulator of proliferative genes. We report that the TEAD-YAP complex is not only frequently hyperactivated in liver and breast cancer, but also confers a strong oncogenic activity in gastric epithelial cells. The increased expression of TEAD-YA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
91
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(93 citation statements)
references
References 59 publications
2
91
0
Order By: Relevance
“…Together with these studies, our current work further demonstrates a complicated machinery for fine and tight control of YAP activity under various cellular contexts. Interestingly, some negative regulators of YAP, such as MST4 kinase characterized here, and the reported SET1A (Fang et al, 2018), RUNX3 (Qiao et al, 2016), and OTUD1 (Yao et al, 2018), were found to be down-regulated in different cancer specimens and to be associated with poor prognosis. Perhaps dysregulation of these YAP-related tumor suppressors could explain the hyperactivation of YAP in cancer cells without apparent change of the classic Hippo kinase cascade.…”
Section: Discussionmentioning
confidence: 51%
“…Together with these studies, our current work further demonstrates a complicated machinery for fine and tight control of YAP activity under various cellular contexts. Interestingly, some negative regulators of YAP, such as MST4 kinase characterized here, and the reported SET1A (Fang et al, 2018), RUNX3 (Qiao et al, 2016), and OTUD1 (Yao et al, 2018), were found to be down-regulated in different cancer specimens and to be associated with poor prognosis. Perhaps dysregulation of these YAP-related tumor suppressors could explain the hyperactivation of YAP in cancer cells without apparent change of the classic Hippo kinase cascade.…”
Section: Discussionmentioning
confidence: 51%
“…In a multivariate survival analysis, Qiao et al found that high TEAD1-4 and YAP1 expressions correlate with a poorer overall survival of GC patients. 15 Nuclear localization of YAP1 was also correlated with a poor outcome in intestinal GC, 24,25 although authors did not find a significant correlation between cytoplasmic expression of YAP1 and survival. 24 In the present study, we showed that expression of YAP1 is heterogeneous inside the primary tumors of GC patients, and we demonstrated that nuclear expression of YAP1 is preferentially found in areas of CD44+ GC cells.…”
Section: Discussionmentioning
confidence: 97%
“…TEAD1 and TEAD4 were upregulated in CD44+ cells, and both proteins were found to be overexpressed in GC 15,27 and associated with a low overall survival in GC (Fig. S1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although many subsequent studies involving thousands of patients have attempted to verify the role of RUNX3 as tumour suppressor gene in gastric cancer and other gastrointestinal tract cancers (Subramaniam et al., ), but, these efforts have failed to confirm whether the RUNX3 is indeed expressed in normal gastrointestinal tract epithelial cells and to determine the quantitative relationship between hypermethylation of RUNX3 promoter regions and its expression (Levanon et al., ). Yet, a recent study has revealed that RUNX3 acts as a tumour suppressor by negatively regulating the TEAD–YAP oncogenic complex in gastric carcinogenesis (Qiao et al., ). In addition, disruption of RUNX3 by miR‐130a and miR‐495 cooperatively increased cell proliferation and tumour angiogenesis in gastric cancer cells, suggesting that RUNX3 inactivation can lead to early gastric tumorigenesis (Lee, Jung, Choi, & Lee, ).…”
Section: Introductionmentioning
confidence: 99%